VENOUS ULCER AND ITS COMPLICATIONS: CASE REPORT 2020 TO 2025 (Editora Impacto Científico, 2025)
This study reports on a case that occurred in 2020, in which a venous ulcer was successfully treated, but after 2025, the wound was again compromised due to myiasis infestation in the municipality of São Lourenço, Minas Gerais. The study demonstrates the relevance of using compressive therapy associated with technological silver foam coverage in the treatment of venous ulcers. Venous ulcers are considered the most serious lesions of Chronic Venous Insufficiency Syndrome (CVI) in the lower limbs, representing a serious public health problem. These ulcers can appear spontaneously or after trauma, and their prevalence is higher than that of other lower limb ulcers, reaching more than 80% of cases. In the case analyzed, the use of compressive therapy, associated with silver foam coverage, proved to be significantly effective in progressing the treatment of the lesion, speeding up the healing process. There was a substantial reduction in wound exposure time, the amount of exudate, local pain and edema, which resulted in a considerable improvement in the patient's quality of life. These advances were essential to encourage treatment of the disease and prevent recurrences, which are common in cases of inadequately treated venous ulcers. Another fundamental point of the study was health education, which played a crucial role in self-care management. Awareness of the disease and proper wound management were key to successful treatment and the prevention of future complications. The study showed that, in addition to physical treatment, patient empowerment through education contributes significantly to improved clinical outcomes and reduced recurrence rates. In short, this study confirms the effectiveness of compressive therapy associated with silver foam in the treatment of venous ulcers, highlighting not only the importance of effective physical treatment, but also the essential role of health education in ensuring adherence to treatment and preventing long-term complications.